Comprehensive Biotechnology 2011
DOI: 10.1016/b978-0-08-088504-9.00256-7
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Engineering of Higher Plants to Produce Bio-Industrial Oils

Abstract: Institute in Saskatoon. Research conducted by his team focuses on trying to understand how plants make oil, what determines the fatty acid composition of oil and how this can be changed for specific end uses. He uses Arabidopsis thaliana and the yeast Sacchromyces cerevisiae as model systems, but also works with oilseed Brassicas, and with Camelina sativa (false flax). Target fatty acids include hydroxy fatty acids such as ricinoleic acid, saturated fatty acids and very long chain fatty acids. Mark obtained hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 41 publications
0
21
0
1
Order By: Relevance
“…Together oilseed rape accounts for around 16% of total vegetable oil production (Gunstone et�al. 2007, Taylor et�al. 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Together oilseed rape accounts for around 16% of total vegetable oil production (Gunstone et�al. 2007, Taylor et�al. 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, C16 and C18 FA are typically found instead of NA in the sn-2 position in the fungus Mortierella capitata RD000969, microalga Mychonastes afer (Umemoto et al, 2014;Fan et al, 2018b). Similar limitation of further increase NA content also occurs in high-EA B. napus and B. carinata and negligible NA is found at the sn-2 position on the glycerol backbone because the ability of endogenous Brassica LPAAT to incorporate nervonoyl moieties into sn-2 position is very low (Scarth and Tang, 2006;Taylor et al, 2011). This bottleneck also limits the content of EA and other VLCFAs as the longer FAs tend to be localized at the sn-1,3 position, which restricts the level of NA, EA or other VLCFAs in the seed oil to a theoretical limit of 66%.…”
Section: Other Optimal Participants In Vlcfa Elongation Are Availablementioning
confidence: 95%
“…The third acylation reaction, converting DAG to TAG, is catalyzed by diacylglycerol acyltransferase (DGAT) enzymes at the sn-3 position using a fatty acyl-CoA (Figure 2) (Kennedy and Weiss, 1956). The research findings showed that NA can only be incorporated into the sn-1 or sn-3 position instead of sn-2 position of TAGs (Scarth and Tang, 2006;Taylor et al, 2011;Umemoto et al, 2014;Fan et al, 2018b).…”
Section: Na Biosynthesis and Assemblymentioning
confidence: 99%
“…This will involve increasing the oil productivity of existing oil crops, introducing additional oilseed crops and creating novel oil production platforms. Metabolic engineering has a central role to play in each of these pursuits and is already making significant contributions to addressing these goals, as has been well reviewed in recent years (Carlsson et al, 2011;Lu et al, 2011;Ohlrogge and Chapman, 2011;Taylor et al, 2011;Weselake et al, 2009). A wide array of metabolic engineering approaches have been employed to increase the oil content in a variety of plant tissues, including diverting carbon flow from starch to TAG, up-regulating fatty acid synthesis, modifying expression of individual TAG biosynthetic enzymes and transcription factors, and slowing the turnover of TAG.…”
Section: Engineering Expanded Oil Productionmentioning
confidence: 99%